Application of Word Square and Scramble Sentence Learning Model to Improve English Vocabulary for Elementary School Students - Salsabila, Revita; Saputra, Erwin Rahayu; Indihadi, Dian (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2022)
This study aims to examine the effectiveness of the application of the word square and scramble sentence learning models as an effort to increase English vocabulary for elementary school students. The method used is a qualitative method with a descriptive analysis approach. Data collection techniques using observation and interview methods. The subjects in this study were class IV students at SDN Sindangreret, totaling 17 people. The data analysis technique uses the Miles & Huberman interactive model. The results of this study discuss 1) student' perspectives on learning English; 2) the stages of learning with the word square and scramble sentence models; and 3) student learning outcomes. The conclusions in this study are 1) the application of the word square and scamble sentence learning models can help students to find and know new vocabulary in English and can improve students' ability to compose vocabulary correctly; 2) the application of the word square and scramble sentence learning models is effective for use in learning activities in elementary schools.